Realising Values Through a Probability Activity (Sains Humanika, 2013)
Values define outlook and attitudes of an individual. Hence, inculcating moral values is of utmost importance to develop the desired behaviour in an individual. Values are a vital part of the affective domain of education including mathematics education. This paper reports a study that aimed to determine the effectiveness of a probability activity in providing experience to students to help them realise the role of the values of ‘humility’, ‘determination’ and ‘perseverance’ in achieving their goals. The comparison of these intended values of the researcher and the students realised values which were based on their written reflections, illustrates the extent to which the activity served its purpose. The results of the study showed that the activity did serve its purpose for the majority of students and hence is suitable to provide experience to students to help them realise the significance of these values.
Keywords: Values; humility; determination; perseverance; probability